Biotissue‐Inspired Anisotropic Carbon Fiber Composite Hydrogels for Logic Gates, Integrated Soft Actuators, and Sensors with Ultra‐High Sensitivity. (15th December 2022) - Li, Shengnan; Yang, Hailong; Zhu, Nannan; Chen, Guoqi; Miao, YueYue; Zheng, Jingxia; Cong, Yang; Chen, Yousi; Gao, Junpeng; Jian, Xigao; Fu, Jun
Abstract: Natural biotissues like muscles, ligaments, and nerves have highly aligned structures, which play critical roles in directional signal transport, sensing, and actuation. Inspired by anisotropic biotissues, composite hydrogels with outstanding mechanical properties and conductivity are developed by compositing thermo‐responsive poly ( N ‐isopropylacrylamide) (PNIPAM) hydrogels with highly aligned carbon fibers (CFs). The anisotropic hydrogels show superior tensile strength (3.0 ± 0.3), modulus (74 ± 7.0 MPa), excellent electrical conductivity (≈670 S m −1 ), and ultra‐high sensitivity (gauge factor up to 647) along CFs, with an anisotropic ratio (AR) up to 740 over those in perpendicular direction. The extremely high AR in conductivity (more than 400) produces high‐level output in parallel direction and low‐level output in perpendicular direction with a direct current (DC) power supply, which is used to fabricate AND and OR gates. Moreover, the composite hydrogels are converted into thermo‐responsive actuators with CFs twisted before compositing with PNIPAM/clay network. The pre‐twisted CF helices impart internal stress that drives reversible actuation of hydrogel helices upon thermo‐stimulating. The actuation is self‐sensed due to the extremely high sensitivity of the composite hydrogels. Such biomimetic anisotropic self‐sensing hydrogel actuators resemble natural biotissues with both actuation and sensing capabilities, and have promise applications for artificial robotics. Abstract : Bio‐inspired anisotropic hydrogels are synthesized by compositing aligned carbon fibers with thermo‐responsive networks. The gels show extremely high anisotropy in modulus, conductivity and sensitivity, and find new use as logic gates. Compositing pre‐twisted carbon fibers with thermo‐responsive network generates 4D helical actuators that sense their own actuations. It shows a promise for human–machine interfacing and soft robots with integrated feedback loop.